Response of hybrid III and Mil-Lx ATD legs to explosively driven vehicle floor loading - Elgy, Ian D.; Williams, Graham H.; Gibson, Charlene S.; Pope, Daniel J. (Journal of biomechanics, 2020)
Results are reported of small-scale explosive experiments with Hybrid III and Mil-Lx anthropomorphic test device (ATD) legs. The legs were subject to loadings from deforming metallic plates, driven by explosive loadings to replicate the movement of the floor of a protected vehicle subject to a land-mine strike. The forces measured by the legs are reported and compared between the two different leg types. The benefits of protective measures, including false-floors and commercially available footpads, are compared for their ability to reduce the forces measured in each leg type. It is concluded that the two leg types respond differently to different protective measures and hence cannot be used interchangeably.